Application of Zeolite-Based Materials for Chemical Sensing of VOCs - Dusan Stosic; Vladimir Zholobenko (Sensors)
Considerable levels of pollution produced by urbanization and industrial development have established a need for monitoring the presence of harmful compounds and the assessment of environmental risks to provide a basis for timely reaction and the prevention of disastrous consequences. Chemical sensors offer a reasonable solution; however, the desired properties, such as high sensitivity, selectivity, stability and reliability, ease of fabrication, and cost-effectiveness, are not always easily met. To this end, the incorporation of zeolites in sensor materials has attracted considerable attention. Such hybrid sensor materials exhibit excellent performances due to the unique properties of zeolites, which have been successfully utilized in gas-sensing applications. In this review, we discuss recent findings in the area of the application of zeolites as sensor materials, focusing on the detection of volatile organic compounds and highlighting the role of zeolite frameworks and the proposed mechanisms in the sensing process. Finally, we consider possible future directions for the development of zeolite-based sensor technology, including the application of hierarchical materials, nanosized zeolites, and 2D material–zeolite heterostructures that would fulfill industrial and environmental demands.